The role of agriculture growth in reducing poverty and hunger: The case of Tanzania - Thurlow, James; Pauw, Karl (International Food Policy Research Institute, 2011)
Although Sub-Saharan Africa experienced unprecedented economic growth in recent decades, this did not always translate into less poverty or improved nutrition. The Tanzanian economy is one example of a country that failed to reap the benefits of sustained rapid growth. National gross domestic product (GDP) grew at 6.6 percent per year during 1998-2007, while agricultural growth, often regarded as instrumental in lowering poverty rates in agrarian-based developing countries, averaged a respectable 4.4 percent during the period. Yet, between 2001 and 2007, Tanzania's poverty rate only fell from 35.7 to 33.6 percent, while the share of the population consuming insufficient calories declined marginally from 25.0 to 23.6 percent.